Research on Key Factors Influencing Surface Subsidence of Paste Backfilling Mining in Thick Coal Seam of Deep Mine - Meng Zhang; Hui He; Xin Jin; Yonglong Qu; Hongjun Guo (Advances in Civil Engineering)
The research on the key factors of surface subsidence in paste backfilling mining of thick coal seam in deep mine is a complex system engineering, which involves mining, backfilling, support, subsidence, safety, and other aspects. At present, there is no systematic research on the key factors of surface subsidence in paste backfilling mining of thick coal seam more than 6 meters in a deep mine. In this paper, field research, laboratory experiments, theoretical analysis, and other research methods are used to carry out the research about 3# coal seam under buildings in the Lu’an area. The main conclusions are as follows: through the construction of the fuzzy extension model of surface subsidence in paste backfilling mining, five types of surface subsidence are obtained, including overburden structure, roof subsidence before backfilling, nonbackfilling account, the strength of filling body, and backfilling technology. It is the key factor to control the surface subsidence; the optimization measures are given to provide a reference for the reasonable design of paste backfilling mining in other working faces. The research conclusion has a certain reference value for solving a series of problems such as coal resources under buildings, solid waste disposal, controlling strata and surface movement, improving the recovery rate of mine resources, and extending the service life of mine.